UI/UX Design Design for Badminton Student Administration System at Anugerah Badminton Club-Pro Medan Badminton Association Based on Mobile Using Design Thinking Method - Febriyana, Rizky; Wulandari, Heni; Putra, Randi Rian (Jurnal ICT : Information and Communication Technologies, 2025)
The digitalization era is a period in which the development of information and communication technology has changed various aspects of human life. One of the impacts of digitalization in the field of sports is the badminton student administration system. As a solution, a website-based administration system was designed to support faster, safer, and more efficient student data management. To ensure that this administration system is effective and in accordance with user needs, the design of UI (User Interface) and UX (User Experience) designs are the main components. The results of this study are This system allows administrators to systematically record student data, including participant information, training schedules, training costs, and progress reports. Some development suggestions include parental access features, training schedules, online payments, reminder notifications, and recording participant achievements. Further development is expected to improve the efficiency and security of student administration at PB. ABC PRO Medan in the digitalization era.